Visualisation of the Litany in Concrete Poetry: Gomringer, Jandl, Bocian - Sadowski, Witold (Porównania, 2021)
The article presents examples of concrete poetry in Polish and German, examples that simultaneously meet the two following criteria: 1) they combine both literary and visual elements, and 2) can be considered as litanies because of the pattern of repetition used. A question is posed as to whether the poems are based on the same concept of space-time as in the medieval litanies. As the analysis shows, inter-semiotic relations between the linguistic and the visual aspects of the poems are indicative of a substantial divergence between Polish and German-language concrete poetry as regards their access to the generic worldview of the litany.